Effects of the Probiotic Mixture Slab51® (SivoMixx®) as Food Supplement in Healthy Dogs: Evaluation of Fecal Microbiota, Clinical Parameters and Immune Function - Rossi, Giacomo; Pengo, Graziano; Galosi, Livio; Berardi, Sara; Tambella, Adolfo Maria; Attili, Anna Rita; Gavazza, Alessandra; Cerquetella, Matteo; Jergens, Albert E.; Guard, Blake C.; Lidbury, Jonathan A.; Stainer, Joerg M.; et al. (Frontiers in Veterinary Science, 2020)
The gut microbiota plays a crucial role in several physiologic functions of the host. In humans and animals, manipulation of the intestinal microbiota by oral administration of probiotic lactic acid bacteria plays a significant role in modulating the immune system. The aim of this study was to evaluate the safety of the probiotic mixture Slab51® and the capacity of this mixture to stimulate immune function in healthy dogs. Twenty dogs were divided in two groups and received a control diet or the same diet supplemented with a dose of 400 billion cfu of lyophilized bacteria for a period of 60 days. Body weight, food intake, body condition score (BCS), fecal score (FSS), fecal immunoglobulin IgA concentration, plasma IgG concentration, and fecal microbiota composition were monitored. Weight, food intake, BCS, FSS, and biochemical parameters remained unchanged during the treatment in both groups of animals. The fecal microbiota showed a significant decrease in the abundance of Clostridium perfringens and a significant increase in the abundance of beneficial Bifidobacterium and Lactobacillus organisms (p<0.05). Fecal IgA and plasma IgG levels were significantly higher in the group receiving the probiotic compared to healthy controls. These data show that dietary supplementation with the probiotic mixture Slab51® is safe and well tolerated, modulating the composition of the intestinal microbiota, and enhancing specific immune functions in healthy dogs.